Investigating the Relationship between Internet Usage and Attitude towards Online Friendship (Case Study: Students of Guilan University) - Mohammad Amin Kanaani; Hamide Mohammadzade; Fateme Mohammadzade (Taḥqīqāt-i Farhangī-i Īrān)
Internet is causing to transform the profile of the everyday life, especially for the youth. Attractiveness of internet has caused that most youth being appealed to the internet friendships, rather than face to face interactions. The present research aimed to investigate the relation between internet usage and attitude towards internet friendship with opposite sex among students. The survey method and researcher constructed questionnaire is used to gather appropriate information. The statistical universe is all under-graduate and post-graduate students of Guilan University, and from among them, 372 students have been selected through proportionate stratified sampling method. The observed positive relations between attitude towards online friendship and internet usage reveal that quantity and quality of internet usage are important variables creating positive attitudes towards online friendships with opposite sex. In accordance with Giddens it can be said that increasing electronic interactions changed traditional attitudes regarding relations between two sexes. The observed relation between the age of students and attitude towards internet friendship reveals the combined effect of time and space factors on changing attitudes. In overall, expansion of internet usage as a part of the process of globalization has an special role on formation of new social meanings such as online friendship with opposite sex, which itself is an apparent feature of modern world.